Implementasi Konsep Community Driven Material Recovery Facilities (C-Dmrf) Sebagai Upaya Penanganan Terintegrasi Sampah Wisata Di Gili Trawangan - Astrini Widiyanti; Siska Ita Selvia; Ramaditia Dwiyansaputra (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
The increase in tourist visits to Gili Trawangan, averaging 1.4% per year, is driven by its distinctive marine tourism attractions and unique socio-cultural appeal. This growth has led to a corresponding rise in waste generation, necessitating the implementation of effective waste management strategies. This community service initiative adopts the Community-based Material Recovery Facility (CdMRF) concept to optimize the performance and governance of the Gili Trawangan Waste Bank. The implementation method is structured into four stages: (1) problem identification and needs assessment, (2) formulation and dissemination of an action plan and standard operating procedures (SOP) for waste management, (3) Training of Trainers (ToT) on CdMRF-based waste management, and (4) training on digital application-based waste management combined with a village-scale organic waste management campaign through composting. The needs assessment identified five waste management subsystems: operational-technical, institutional, policy and regulatory, financial, and socio-community aspects. The CdMRF implementation is tailored to local policies, engages stakeholders, and promotes recycling at the neighborhood level. Digital application-based training enhances management transparency and efficiency, while composting campaigns strengthen organic waste management practices. The results indicate that CdMRF implementation has increased community participation, reinforced institutional capacity, and supported integrated and sustainable tourism waste management.